Performance Evaluation of Friction Materials for Railway Brake Application Using Oil Palm Empty Fruit Bunch Fiber as Reinforcement - Alam, H.S.; Puja, IGN W.; Suratman, R. (Teknologi Indonesia, 2012)
Performance of friction material for railway brake applications using oil palm empty fruit bunches (OPEFB) fibers as reinforcement has been evaluated using extension evaluation method (EEM) refers to the technical specifications of PT. KAI. Characterizations of two commercial samples, K1 and K2, were used as a reference and a preliminary study to develop railway brake materials using OPEFB fi bers. Six samples of non-commercial brake that use OPEFB fi bers, T1 to T6, were made with different compositions and then tested with samples of K1 and K2. The results of the tests were used as input of evaluation to select the best samples of brake material. Base on the results of evaluation using EEM, samples T1 and T4, which used OPEFB fi bers as reinforcement ranked above the commercial sample K2 which used synthetic fi bers, so it can be concluded that OPEFB fi ber as reinforcement for railway brakes can improve the physical and mechanical properties, have excellent performance, friendly to the environment and is expected to replace synthetic fibers.